2016
DOI: 10.5433/1679-0359.2016v37n2p1029
|View full text |Cite
|
Sign up to set email alerts
|

Energy and protein requirements of crossbred cattle in feedlot

Abstract: The objective of this study is to predict the energy and protein requirements of crossbred dairy cattle in feedlot. The study was conducted at the Unidade Acadêmica de Serra Talhada, Universidade Federal Rural de Pernambuco, Brazil with 30 bulls with a body weight of 339.1 ± 35.4 kg. Five animals were slaughtered at the end of the adaptation period to serve as the reference group; the remainder of the animals was slaughtered after 112 days. The latter group was randomly allocated to receive five treatments: 0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…This assertion can be corroborated with results found by Neves et al (2016), who reported similarity in the nutritional requirements of dairy-origin male bovines when compared to Nelore and its crossbreeds. This means that dairy-origin bovines (Holstein-Zebu) present organs + viscera weight, carcass characteristics and cut weights similar to those of Nelore and its crossbreeds, which directly reflects on the parity of nutritional requirements.…”
Section: Resultssupporting
confidence: 80%
“…This assertion can be corroborated with results found by Neves et al (2016), who reported similarity in the nutritional requirements of dairy-origin male bovines when compared to Nelore and its crossbreeds. This means that dairy-origin bovines (Holstein-Zebu) present organs + viscera weight, carcass characteristics and cut weights similar to those of Nelore and its crossbreeds, which directly reflects on the parity of nutritional requirements.…”
Section: Resultssupporting
confidence: 80%